The Influence of Work Discipline, Work Motivation and Career Development on Alfamart Employee Performance in Batam City - Arsyila Dayu Sahestan; Hikmah Hikmah (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Human resources are considered as important assets in a company. Human resource management (HRM) has the responsibility to develop positive employee behavior and optimize the best performance for the company and the employees themselves. Employee performance includes the work methods used to achieve results and individual achievements in completing the tasks given. This study aims to analyze the effect of work discipline, work motivation, and career advancement on the performance of Alfamart employees in Batam City. The population of the study was Alfamart employees in Batam City with a sample of 110 respondents selected randomly. The research method applied in this study uses a quantitative method conducted through a survey by distributing questionnaires. This research test uses validity tests, multicollinearity tests, reliability, coefficient of determination, and hypotheses. Data processing is carried out by applying multiple linear regression analysis using SPSS version 30 software. The results of the analysis show that simultaneously work discipline, work motivation, and career advancement have a positive and significant effect on employee performance. This study confirms that increasing work discipline, work motivation and career advancement opportunities can effectively improve employee performance. The practical implications of this study suggest that to maximize employee performance, Alfamart management should focus on improving work discipline through firm policies, increasing motivation with appropriate rewards, and offering clear career advancement prospects.